PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) ELEKTRONIK BERBASIS LITERASI SAINS PADA MATERI EKOSISTEM KELAS X SMA - Hotmita Br Regar; Yuslim Fauziah; Fitra Suzanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to produce an electronic Student Worksheet (LKPD) based on Science Literacy in High Quality Class X High School Ecosystem Materials. The research was carried out at the Biology Education Study Program, FKIP UNRI, a zoom meeting platform and at school for SMA Negeri 2 Pekanbaru students from July to November 2021. The subject of this research was KD 3.9 ecosystem material for class X SMA. The type of research used is the ADDIE Research and Development model. The instrument used is a validation sheet. The validation sheet consists of 3 aspects, namely the design aspect, the pedagogic aspect and the content feasibility aspect. The results of the validation of the electronic LKPD based on Science Literacy on Ecosystem Materials for Class X SMA shows that the electronic LKPD that has been developed is in the very valid category with an overall average score of 3.40. The three aspects include design aspects with an average of 3.55, pedagogic aspects with an average of 3.26, aspects of content feasibility with an average of 3.39. The aspect that gets the highest score is the design aspect with an average score of 3.55 which is in the very valid category. The results of the trial phase I obtained an average score of 3.64 and the results of the trial phase II obtained an average score of 3.82 with a very good category. The results showed that the electronic LKPD that was developed was good and suitable to be used as a learning reference in schools as well as a source of independent learning to increase students' knowledge and understanding of ecosystem materials in facilitating students to build their own knowledge.Key Words: Electronic Student Worksheet, Science Literacy, Ecosystem.